Strategi Marketing Politik Caleg Muslim dalam Pemilihan Legislatif Tingkat Kabupaten/Kota: Studi Kasus DPD Partai Amanat Nasional di Kabupaten Karo - Widia Putri Br Ginting (Pusat Studi Pesantren dan Pemberdayaan Masyarakat, LPPM, Universitas Brawijaya, 2021)
This study aims to find out how the political marketing strategy of muslim legislative candidates from the Partai Amanat Nasional (PAN) to win the 2019 Legislative Election at the district/city level in Kabupaten Karo. This is interesting to analyze because the voters in Kabupaten Kao embraced Christianity and two of the three candidates from PAN who sat in the Kabupaten Karo DPRD seats embraced Islam. The research method used is a qualitative descriptive method. Marketing strategy carried out by Muslim candidates from the Partai Amanat Nasional by forming a successful team where they will help campaign for the vision/mission of the candidates. In carrying out the promotion of legislative candidates, socialization is carried out in two ways, namely offline by installing the attributes of candidates and parties, also conducting face-to-face socialization with voters, and also carrying out a cultural approach, online by joining groups on Facebook. For the campaign or promotion to run smoothly, voter mapping is carried out, determining the vote base and also prospective voters during the legislative elections. The cost issued by one of the legislative candidates for the 2019 legislature is 400 million to 600 million.